Analysis the Performance of Hydrophilic and Corrosion Resistant Coatings on the Distillation Desalination Tube in High Temperature Seawater. Issue 1 (December 2021) - Lv, Jiang; Chen, Zhi-li
Abstract: Distillation desalination can use solar energy and other renewable energy, it is one of the most potential technologies for desalination. However, distillation desalination system pervades problems such as low desalination efficiency and poor corrosion resistance. Based on our preliminary study (i.e., apply hydrophilic modification on the surface of distillation desalination tube can effectively improve desalination efficiency), this paper introduces a composite functional coating with the micro-arc oxidation (MAO) coatings sealed with hydrophilic organic coating-TiO 2 hybrid sols (OT-MAO) by sol-gel process. Through contact angle measurement, scanning electron microscopy (SEM) and potentiodynamic polarization test to analyze and compare the performance of hydrophilicity and corrosion resistance of the MAO coatings and the OT-MAO composite coatings in high temperature seawater environment. The corrosion mechanism of the OT-MAO composite coatings was analyzed by electrochemical impedance spectroscopy (EIS). The results show that the OT-MAO composite coatings in high temperature seawater has much better hydrophilicity and corrosion resistance than the MAO coatings. This paper provides theoretical and technical reference for developing a new type of surface modified distillation desalination tube.